1999
DOI: 10.1103/physreve.60.7098
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of random packing of unequal particles

Abstract: A Monte Carlo simulation model for the random packing of unequal spherical particles is presented in this paper. With this model, the particle radii obeying a given distribution are generated and randomly placed within a cubic packing domain with high packing density and many overlaps. Then a relaxation iteration is applied to reduce or eliminate the overlaps, while the packing space is gradually expanded. The simulation is completed once the mean overlap value falls below a preset value. To simulate the rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(126 citation statements)
references
References 30 publications
5
119
1
1
Order By: Relevance
“…For g ¼ 2:6 we found f max ¼ 0:691. The simulation data reported by He et al [15] found f max for x 2 equal to 0.340 and 0.400 for size ratios 2.0 and 1.5, respectively, which significantly differs from x 2 ¼ 0:275 found in our results.…”
Section: Packing Densitiescontrasting
confidence: 57%
See 2 more Smart Citations
“…For g ¼ 2:6 we found f max ¼ 0:691. The simulation data reported by He et al [15] found f max for x 2 equal to 0.340 and 0.400 for size ratios 2.0 and 1.5, respectively, which significantly differs from x 2 ¼ 0:275 found in our results.…”
Section: Packing Densitiescontrasting
confidence: 57%
“…These tests are similar to the tests in Ref. [15]. The system we will present below consists of 10,976 particles where 80% of the particles are small spheres (x 2 ¼ 0:18).…”
Section: Appendix a Randomness Homogeneity And Isotropymentioning
confidence: 49%
See 1 more Smart Citation
“…It was already shown that improvements in the compaction of the particles can be accomplished when one shakes the formed aggregate, yielding particle packings with the highest densities. However, a sufficient time is required to achieve the saturation density [23], which depends on the shake amplitude. From previous numerical and experimental works [39], this saturation density increases as the shake amplitude decreases.…”
Section: Resultsmentioning
confidence: 99%
“…Significant contributions in the study of these processes were given by Yen and Chaki [13], Cheng et al [15] and Yang et al [14] using DEM. Collective rearrangement models [20][21][22][23][24] have also been used to simulate particle random packing. More recently, Jia et al [16] used DEM to study fine particle packing with Gaussian size distributions.…”
Section: Introductionmentioning
confidence: 99%